TRANSFORMATIONAL LEADERSHIP STYLE IN IMPROVING EMPLOYEE PERFORMANCE: A LITERATURE REVIEW - Fahrudin, Rizal (Jurnal Manajemen Dan Bisnis, 2025)
In an increasingly dynamic organizational environment, transformational leadership has been recognized as a crucial leadership style for improving employee performance. This study aims to deeply examine the influence of transformational leadership style on employee performance through a literature review. The research method used is a literature review, which involves collecting, reviewing, and analyzing various relevant scientific references such as journals, books, and research articles. The review results indicate that transformational leadership significantly enhances employee performance. Transformational leaders can provide inspiration and motivation, and pay attention to the individual needs of subordinates, thus encouraging employees to contribute optimally. This leadership style is characterized by four main dimensions: idealized influence (leaders as role models of integrity and ethics), inspirational motivation (leaders inspire with a clear vision), intellectual stimulation (leaders encourage critical thinking and innovation), and individualized consideration (leaders provide personal attention for employee development). The implementation of transformational leadership has been shown to increase intrinsic motivation, work quality, sense of responsibility, and employee loyalty. Furthermore, this style also creates a work environment that is integrated, productive, collaborative, and adaptable to rapid changes. Challenges in implementation include the need for a supportive organizational culture. Overall, transformational leadership is a key driver in achieving sustainable productivity and work effectiveness, as well as strengthening organizational competitiveness. This research provides theoretical and practical contributions to the development of human resource management science.